The Public Tradition of Philanthropy on Vasilievsky Island in the Second Half of XIX - early XX Centuries (On Materials of Personal Archive of T. S. Bleszko (Pavluchin)) - Olga Borisovna Vakhromeeva (Управленческое консультирование)
In this article we are talking about the initiative of merchants, who lived on Vasilievsky island in the capital in the second half of XIX - early XX century, aimed at the establishment of a charitable society at St. Andrew Orthodox Cathedral. Materials the articles were derived in the personal archive of Tatiana Sergeevna Blaszko (nee Pavlukhin) (St. Petersburg), the granddaughter of one of active participants of a charitable organization. All members of society were socially significant people, but nevertheless several times a week walked the land entrusted to them with the aim to interview most of the residents have suffered for far Vasilievsky island. Assistance provided firewood, money, educated the children, organized charity and shelter, held a charity evening, provided cheap housing, etc. The importance of merchants and public figures devoted to the education of children (they set up two of the shelter) and care of sick and frail old people (there was a women’s shelter etc.).